Antagonism by Phentolamine and Yohimbine not Hydralazine on Noradrenaline-Induced Hypertension in Rat - Songkittiguna, Prasert; Jindagul, Giatbungon (Journal of Basic and Applied Pharmacology, 2015)
Noradrenaline (10 mcg, IV) increases blood pressure of anaesthetized rats with little effect on heart rate. Pretreatment of the rat with hydralazine (2 mg/kg IV) could not inhibit the noradrenaline-induced hypertension in the rats. Both phentolamine (2 mg/kg IV) and yohimbine (0.25 mg/kg IV) not only reduce the blood pressure of anaesthetized rats significanlly (p ≤ 0.05) but also inhibits /lie hypertensive effect of noradrenaline (10 mcg, IV). Phentolamine (2 mg/kg IV), neither hydralazine nor yohimbine pretreatment, significantly decreased the heart rate of the anaesthetized rats (p ≤ 0.05) from the predrug value. The findings suggest, therefore, that hydralazine is not suitable for the treatment of noradrenaline-induced hypertension.